Four‐way waveguide power divider design for W‐band applications. Issue 5 (17th January 2018) - Li, Jianxing; Li, Lei; Lu, Ling; Shi, Hongyu; Huo, Huimin; Zhang, Anxue
Abstract: In this article, a four‐way waveguide power divider is proposed for W‐band applications. The waveguide power divider employs an improved H‐plane T‐junction configuration. With the introduction of a metallic tetrahedral protrusion into the waveguide junction, good impedance matching can be achieved within a wide frequency range. First, a two‐way power divider is designed and analyzed, achieving almost identical amplitude and phase response at its two output ports. Then, other two same T‐junctions are cascaded, respectively, at the two output ports of the two‐way power divider to realize the proposed four‐way power divider. The four‐way power divider has been optimized, fabricated, and measured. The measurement results agree with the simulation ones reasonably, which demonstrates that the input return loss of the proposed four‐way power divider maintains above 14 dB across the entire W‐band with an insertion loss of less than 1.3 dB. Therefore, it could find wide applications in W‐band power splitting and combining modules.